Escolarização e profissionalização na medida socioeducativa de internação no Paraná -o discurso do protagonismo juvenil nos cadernos de socioeducação - Farias , Lilian Cristina Penteado de (2015)
This dissertation investigates the Schooling and Professionalization of teenagers attended by the National Socioeducational Services Policy, especially for Socioeducational Measure of Internment in Paraná, Brazil. The bibliographical and documentary research is about the Socioeducational Measure of Internment from the Law No. 8069, July 1990, Child and Adolescent Statute - ECA; from National System of Socioeducational Services - SINASE (BRAZIL, 2006); from Law No. 12,594 of January 2012, which regulates the SINASE; and Notebooks of Socioeducation: Understanding Adolescents (2010a) (Compreendendo o Adolescente); Socioeducational Center Management (2010b) (Gestão de Centro de Socioeducação); Practices of Socioeducation (2010c) (Práticas de Socioeducação); Security Routines (2010d) (Rotinas de Segurança); e Crisis Management in Socioeducational Centers (2010e) (Gerenciamento de Crises nos centros de Socioeducação). The specific objectives are: a) To characterize the Socioeducational Measure of Internment from the documents that give the National Socioeducational Services Policy livelihood in the legal and organizational field. b) Unveiling the process of implementing the set of Notebooks of Socioeducation (2010) by tracing the history of care for the adolescent who commits an infraction in Paraná, Brazil. As a result of investigations it was found that all the Notebooks of Socioeducation (2010) presents foundation in the Youthful Protagomism, where the teenager is summoned to take advantage of positive opportunities offered in the period that fulfills the Socioeducational Measure of internment. The Youthful Protagonism appears in Notebooks of Socioeducation (2010) associated with the terms competence, skills, emancipation, is a precondition to the Socioeducational Service in the state of Paraná, supported by Schooling programs and Professionalization.